Melampolides from Enydra anagallis - Bardon, Alicia del Valle (2001)
The investigation of an Argentine collection of Enydra anagallis afforded sesquiterpene lactones of the melampolide type two of which were previously known. Their structures were elucidated by spectroscopic methods.